Particle Detectors, Second Edition - Grupen, Claus (Cambridge University Press, 2008)
Elementary particles can be identified through various techniques, depending on the purpose of the measurement and which relevant quantities, such as time, energy, and spatial coordinates, have to be measured. Detectors cover the measurement of energies spanning from the very low to the highest energies observed in cosmic rays. Describing the instrumentation for experiments in high energy physics and astroparticle physics, this edition describes track detectors, calorimeters, particle identification, neutrino detectors, momentum measurement, electronics, and data analysis. It also discusses applications of these detectors in other fields, such as nuclear medicine, radiation protection, and environmental science. Problem sets have been added to each chapter and additional instructive material has been provided, making this an excellent reference for graduate students and researchers in particle physics.